The Turnip, The New Husbandry, and The English Agricultural Revolution - Timmer, C. Peter (Quarterly Journal of Economics, 1969)
Introduction, 375. — The traditional view, 377. — The modern view, 380. — The new husbandry, 385. — Labor requirements, 392. — Conclusion, 394.